Enhancing the quality of human resource training activities at Hanoi regional Branch of Deposit Insurance of Vietnam - Pham, Phuc Dang Khoa (Khoa Quốc tế, ĐHQGHN, 2019)
This thesis aims to explain the relationship between human resource training and business development, by collecting data and reporting data from the Hanoi branch as an example to propose solutions to increase human resources at the branch